Solve for x :ap^(bx+c) -d =0?
solve for x: ap^(bx+c) -d =0
when p; a; d > 0; b cannot equal 0; ceR
- Jeff AaronLv 78 years agoBest Answer
ap^(bx + c) - d = 0
ap^(bx + c) = d
p^(bx + c) = d/a
log (base p) of (d/a) = bx + c
bx = (log (base p) of (d/a)) - c
x = ((log (base p) of (d/a)) - c) / b
- theronLv 43 years ago
difficulty a million: Use the quadratic formulation. x = [ -b ± ?(b² - 4ac) ] / 2a a = a million b = a million c = -3 x = [ -a million ± ?(a million² - 4(a million)(-3)) ] / 2 x = [ -a million ± ?(13) ] / 2 answer: x = -a million/2 ± (?13)/2 difficulty A: Quadratic formulation back with a = 5, b = -4, c = a million. you attempt this one on your man or woman... difficulty B: 9x² = 14 x² = 14/9 x = ± ?(14/9) x = ± (?14) / 3 difficulty C: Take the sq. root of the two sides: x + 5 = ± ?3 x = -5 ± ?3 difficulty D; Quadratic formulation difficulty E: See difficulty a million.